The Influence of Work Environment and Organizational Commitment on Employee Performance with Motivation as a Mediating Variable at the Population and Civil Registration Service of Gresik Regency - Sriyanto; Djoko Soelistya (Al-Kharaj: Journal of Islamic Economic and Business, 2024)
The purpose of this study was to analyze and test the influence of work environment and organizational commitment on employee performance with motivation as a mediating variable at the Population and Civil Registration Service of Gresik Regency directly and indirectly. The approach used in this study is a causal approach. The population in this study were all employees of the Population and Civil Registration Service of Gresik Regency. The sample in this study used a saturated sample of 107 from all employees of the Population and Civil Registration Service of Gresik Regency. The data collection technique in this study used documentation, observation, and questionnaire techniques. The data analysis technique in this study used a quantitative approach using statistical analysis with the Outer Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study used the PLS (Partial Least Square) software program. The results of this study prove that 1) the work environment does not affect employee performance, 2) organizational commitment affects employee performance, 3) the work environment affects employee performance, 4) organizational commitment affects employee performance, 5) motivation affects employee performance, 6) the work environment can improve employee performance through motivation, and 7) organizational commitment cannot improve employee performance through motivation.